Taking “Gout” as an Example, a New Model of Disease Science Popularisation in the Era of Integrated Media - Ai, Meichen; Wei, Jinli; Li, Wanfen; Zhuang, Jian; Yang, Fangyuan; Li, Jie; He, Yi (Journal of clinical rheumatology and immunology (Online), 2024)
Background: Statistics indicate that there are approximately 200 million individuals with hyperuricemia and 20 million people suffering from gout within my country. The general public is lack of awareness of the risks associated with gout. Many primary hospitals lack the capacity to correctly diagnose and treat gout, resulting in the inefficient use of national medical resources and significant distress and economic hardship for patients. Consequently, the expeditious and efficacious dissemination of gout science knowledge to the general public is of considerable social and economic consequence. Methods: The project team employs a rational integration of online platforms, newspapers, and other resources, in both online and offline modes, and promotes gout medical science knowledge through the utilization of new integrated media science popularisation models. Results: The project leader created the personal IP of “Dr. He Yi” with a cumulative fan base of over 2 million across the entire network. He was awarded one science popularisation project of the Guangdong Province Science and Technology Plan and two science popularisation projects of the Guangzhou City Science and Technology Plan. As the editor-in-chief, he published the popular science book “Dr. Tiantian Talks about Rheumatism-Gout”. As of May 2022, more than 600 popular science articles have been published, more than 200 popular science videos have been released, and 3 training and teaching videos have been recorded; the cumulative number of visits has exceeded 200 million times. Nearly 100 free clinics, science popularisation lectures, and grassroots doctor training have been conducted. The project leader was awarded several honours, including the “2023 Sohu Video Top Ten Broadcasters of the Year” accolade, the “2020 Chinese Medical Doctor Association Health Communication Working Committee n Kwai, Comprehensive Doctors and Science popularisation Contribution Award”, and the “2020 Baidu Health Live Broadcast Top Ten”. Additionally, the project was recognised with the “Guangdong Provincial Medical Science and Technology Award, Popular Science Award”. Conclusion: The project team proposed a novel model of “integrated media” for the popularisation of medical science. This model is not merely the integration of newspapers and online media, nor is it simply the integration of popular science articles, videos, and books. It also encompasses the integration of free clinics, popular science lectures, grassroots doctor training, MDT diagnosis and treatment teams, and new “three habitats” medical talent training. This model improves patients’ quality of life, reduces patients’ economic burden, conserves health care resources, and contributes to national health.